Designing learning experiences using the R-C-A questioning technique to instill moral values and develop cognitive skills in early childhood - Amphandaeng, Ritthichai (Mahachula Academic Journal, 2026)
This research aimed to 1) examine the effects of learning experience management using the R-C-A (Recall–Connect–Apply) questioning technique on the development of moral attributes and executive functions (EF) of early childhood students, and 2) compare the levels of moral attributes and EF before and after the implementation. The study employed a pre-experimental design using a one-group pretest–posttest approach. The sample consisted of 16 early childhood students in the academic year 2024 at Bankhaoman School under Prachuap Khiri Khan Primary Educational Service Area Office 1. The research instruments included: 1) 15 learning experience plans using the R-C-A questioning technique integrated with Active Learning activities, and 2) data collection tools, namely an EF assessment focusing on inhibitory control and attention, and an observation form for basic moral behaviors. Data were analyzed using mean, standard deviation, percentage, and dependent t-test. The results revealed that: 1) students’ basic moral attributes—discipline, responsibility, and kindness—improved continuously, with the overall mean increasing from 82.22% to 93.78%. Similarly, EF skills in inhibitory control and attention increased from 80.80% to 88.00%; and 2) after the intervention, students demonstrated significantly higher levels of moral attributes than before at the .05 level (mean increased from 1.80 to 2.74; t = 23.37, p = 0.00). Likewise, EF levels significantly increased at the .05 level (mean increased from 2.92 to 4.23; t = 8.17, p = 0.00). These findings indicate that learning experience management using the R-C-A questioning technique effectively enhances both moral attributes and executive functions in early childhood learners.